PROMOTING COGNITIVE GROWTH IN YOUNG CHILDREN THROUGH PRESCHOOL EDUCATION - Riskieva Mutabar Hakimovna (Western European Studies, 2024)
Cognitive development during early childhood is crucial for intellectual growth, with preschool education playing a vital role in nurturing this process. High-quality early education fosters critical thinking, problem-solving skills, and social competence through structured teaching methods. Guided by theories such as Piaget’s stages of development and Vygotsky’s Zone of Proximal Development, preschool programs emphasize active learning, social interactions, and hands-on activities to promote language, memory, and logical reasoning. Approaches like Montessori and Reggio Emilia highlight self-directed learning and collaboration, supporting cognitive and social growth. By integrating problem-solving tasks, scaffolding, and imaginative play, preschool education establishes a foundation for lifelong learning and success.
Keywords: Cognitive development; Early childhood; Preschool education